Development and Optimization of a Nanoparticle-Based Imidacloprid Insecticide for Effective Control of Blattella germanica - Ismael Saba; Amir Amani; Mozhgan Baniardalani; Hamidreza Basseri (Journal of Arthropod-Borne Diseases)
Background: The German cockroach (Blattella germanica) is a pest with a global distribution that has adapted to live in human environments. Blattella germanica threatens human health by producing asthma-inducing allergens, carrying pathogenic/antibiotic-resistant microbes, and contributing to unhealthy indoor environments. Effective application of insecticides can play an important role in cockroach control programs. The purpose of this research was to develop and optimize a nanoparticle-based imidacloprid insecticide and evaluate its effectiveness against the German cockroach.